2020
DOI: 10.3390/s21010057
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of Adventitious Respiratory Sounds: A (Un)Solved Problem?

Abstract: (1) Background: Patients with respiratory conditions typically exhibit adventitious respiratory sounds (ARS), such as wheezes and crackles. ARS events have variable duration. In this work we studied the influence of event duration on automatic ARS classification, namely, how the creation of the Other class (negative class) affected the classifiers’ performance. (2) Methods: We conducted a set of experiments where we varied the durations of the other events on three tasks: crackle vs. wheeze vs. other (3 Class)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…of normal breathing sounds and various types of adventitious sounds [38,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. The models in most of these studies are developed on the basis of an open-access ICBHI database [20,21].…”
Section: Plos Onementioning
confidence: 99%
“…of normal breathing sounds and various types of adventitious sounds [38,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. The models in most of these studies are developed on the basis of an open-access ICBHI database [20,21].…”
Section: Plos Onementioning
confidence: 99%
“…It has also been shown that the use of spectrograms can improve the classification of wheezes and crackles in an educational setting [ 23 ]. On the other hand, the automatic classification of adventitious respiratory sounds is still an ongoing problem [ 24 ]. Currently there are no public databases available to evaluate and compare new algorithms, but the creation and public release of such databases will be useful to solve the respiratory sound classification problem [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…ss5: Update the estimated wheezing activations matrix A W using Equation (16). ss6: Update the estimated respiratory activations matrix A R using Equation (17). ss7: Repeat Steps 3-6 until the algorithm converges (or until the maximum number of iterations M is reached).…”
Section: Low-rankmentioning
confidence: 99%
“…Continuous Adventitious Sounds (CASs) are characterized by a long duration of more than 100 ms, such as rhonchi, stridor, and wheezing [14]. In recent years, several works have been published that carried out an exhaustive review of lung acoustic measurements [15] and signal processing methods [16,17] applied to adventitious sounds, most of them focused on detection [16][17][18][19][20][21][22][23] and classification tasks [16,17,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%